2013
DOI: 10.14778/2536222.2536235
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and big data scale parallel execution in oracle

Abstract: This paper showcases some of the newly introduced parallel execution methods in Oracle RDBMS. These methods provide highly scalable and adaptive evaluation for the most commonly used SQL operations -joins, group-by, rollup/cube, grouping sets, and window functions. The novelty of these techniques is their use of multi-stage parallelization models, accommodation of optimizer mistakes, and the runtime parallelization and data distribution decisions. These parallel plans adapt based on the statistics gathered on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Kim [10] and Morzy [11] described the transformation of logical sets (magic set), which leads to new insights into the costly units' request, thus allowing the volume of data being processed to be reduced.…”
Section: Related Workmentioning
confidence: 99%
“…Kim [10] and Morzy [11] described the transformation of logical sets (magic set), which leads to new insights into the costly units' request, thus allowing the volume of data being processed to be reduced.…”
Section: Related Workmentioning
confidence: 99%
“…The 64 available hardware threads are distributed uniformly over the streams, and each stream executes random permutations of the TPC-H queries. Figure 12 shows that the throughput stays high 6 In practice, the database itself is located on a single NUMA node, because the data is read from disk by a single thread. Other allocations are local to the thread that first wrote to that memory.…”
Section: Elasticitymentioning
confidence: 99%
“…Very similar to Volcano-style parallelization, in Oracle the individual operators are largely unaware of parallelism. [6] addresses some problems of this model, in particular reliance on query optimizer estimates, by adaptively changing data distribution decisions during query execution. In an experimental study Kiefer et al [17] showed that NUMA-awareness can improve database performance considerably.…”
Section: Related Workmentioning
confidence: 99%
“…Traditionally, in relational DBMS, window functions have been commonly used for data analytics [7,1]. Instead of performing analysis (e.g.…”
Section: Introductionmentioning
confidence: 99%